Effets déclarés par les acteurs à propos du dispositif « devoirs faits » dans un collège - Teresa Assude; Karine Millon-Faure; Claire Guille-Biel Winder; Julie Gobert (Éducation et Socialisation)
The « homework done » (« devoirs faits ») devise has been in place in french « collèges » since 2017. As a part of a research project on monitoring and accompanying this implementation in a « REP + Collège ») in Marseille, we are interested in what actors (students, teachers and education assistants) report on the perceived effects of this type of devise, difficulties and obstacles encountered.